Students' beliefs on English language anxiety in learning English as second language / Maizatul Faranaz Md Asif - Md Asif, Maizatul Faranaz (2014)
This study is an attempt to investigate the students' perceptions on English language anxiety in learning English as a second language. English Language Anxiety Scale, (ELAS) developed by Pappamihiel, (2002) is used to investigate: 1) What is the relationship between gender and level of English language anxiety?, 2) Is there any connection between classroom setting( the usage of English in regular classroom or English classroom) and level of English language anxiety?, 3) What are the factors that contribute to anxiety in learning English as second language?, 4) What are the strategies that can be employed to reduce anxiety in learning English as second language? and 5) What are the students beliefs toward language anxiety in learning English as second language? This research involves 50 secondary school students and the analysed data have shown that majority of the students have high level of English language anxiety and the biggest contributor islearner factor . Thus this research specifically provide substantiated information for both teachers and students in handling and reducing anxiety in learning English as second language in order to enhance the success of second language learning.